Case reportGranular cell meningioma. A case report - Lach, Boleslaw; Kanaan, Imaduddin (Folia Neuropathologica, 2007)
We describe a granular cell tumour developing in clear cell meningioma of the falx. Granular and clear cells showed immunoreactivity for vimentin, epithelial membrane antigen and progesterone receptors. This is the first case documenting arachnoid origin of neoplastic granular cells in meningioma.